A simple assay of intrinsic factor-vitamin B(12) complex employing the binding intrinsic factor antibody - Jacob, Elizabeth (1972)
The reaction between binding intrinsic factor antibody and intrinsic factor-vitamin B(12) complex has been studied. Initially in the zone of antibody excess, the relationship between the amount of antigen present and the amount of antigen-antibody complex adsorbed onto zirconium phosphate gel was linear. With increasing amounts of antigen, the curve departed from linearity and reached a plateau. The linear portion of the reaction forms the basis of a simple and reproducible assay for quantitating intrinsic factor to which vitamin B(12) has already been bound. The assay provides a method for studying the fate of intrinsic factor-vitamin B(12) complex during digestion and absorption. In two normal subjects given radioactive vitamin B(12) orally, aspiration of ileal contents showed that only 50 to 70% of the radioactivity was bound to intrinsic factor at that level.